Rapid neonatal hearing screening using modified automated auditory brainstem response maximum length sequences - Dzulkarnain, Ahmad Aidil Arafat; Wilson, Wayne; Bradley, Andrew; Petoe, Matthew; Moon, Jackie (2007)
Universal Newborn Hearing Screening (UNHS) is an important tool for detecting hearing impairment in newborns, but it is often hindered by unacceptably long test times. This paper will describe a preliminary data set obtained from 100 newborns using a new form of automated auditory brainstem response (AABR): a non-linear maximum length sequence (MLS) AABR with automated analysis. Initial analyses of this data suggest this new AABR test can reduce average screening times from minutes to a few seconds per newborn. The implications of this data and the possibilities for future research will be discussed.